Evolutionary implications of C2 photosynthesis: how complex biochemical trade-offs may limit C4 evolution. (28th November 2022) - Walsh, Catherine A; Bräutigam, Andrea; Roberts, Michael R; Lundgren, Marjorie R
Abstract: The C2 carbon-concentrating mechanism increases net CO2 assimilation by shuttling photorespiratory CO2 in the form of glycine from mesophyll to bundle sheath cells, where CO2 concentrates and can be re-assimilated. This glycine shuttle also releases NH3 and serine into the bundle sheath, and modelling studies suggest that this influx of NH3 may cause a nitrogen imbalance between the two cell types that selects for the C4 carbon-concentrating mechanism. Here we provide an alternative hypothesis outlining mechanisms by which bundle sheath NH3 and serine play vital roles to not only influence the status of C2 plants along the C3 to C4 evolutionary trajectory, but to also convey stress tolerance to these unique plants. Our hypothesis explains how an optimized bundle sheath nitrogen hub interacts with sulfur and carbon metabolism to mitigate the effects of high photorespiratory conditions. While C2 photosynthesis is typically cited for its intermediary role in C4 photosynthesis evolution, our alternative hypothesis provides a mechanism to explain why some C2 lineages have not made this transition. We propose that stress resilience, coupled with open flux tricarboxylic acid and photorespiration pathways, conveys an advantage to C2 plants in fluctuating environments. Abstract : An alternative theory for bundle sheath ammonia tolerance in C2 species suggests that C2 to C4 evolutionary transitions may depend on bundle sheath nitrogen hub optimization.